2020
DOI: 10.1111/odi.13287
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline ring granuloma of the mouth—A foreign‐body reaction that dentists should be aware of

Abstract: Hyaline ring granuloma (HRG) is a rare and atypical foreign‐body granulomatous chronic inflammatory condition. Our aim was to make a critical review of the literature cases and also to illustrate histochemical and immunohistochemical findings of a new case. A modified PICO strategy was used. Inclusion criteria were met by case reports and case series with a histologically confirmed diagnosis of HRG, necessarily in mouth or maxillary bones. Exclusion criteria were no access to the full‐text paper. The search wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(193 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, Shimamura et al reported that inflammation was present at the sites of foreign bodies 15 . Foreign bodies might occur hyaline ring granuloma, which is a rare and atypical granulomatous chronic inflammatory condition 24 . We should judge the timing of removal comprehensively from the viewpoint of the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Shimamura et al reported that inflammation was present at the sites of foreign bodies 15 . Foreign bodies might occur hyaline ring granuloma, which is a rare and atypical granulomatous chronic inflammatory condition 24 . We should judge the timing of removal comprehensively from the viewpoint of the factors mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Oral pulse granuloma is a rare entity in which no features considered clinically pathognomic of pulse granuloma and remains largely a microscopic diagnosis. 13 A more widespread knowledge on the unusual sites of occurrence and clinical manifestations may aware the clinicians about the diagnostic hazard of mistaking pulse granulomas for other entities. For clinicians, it is very useful to know hyaline ring granuloma, not only because other diseases (which require different therapeutic approaches) can mimic it, leading to misdiagnosis of relevant impact, but also because some clinical situations increase the risk of its occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors consider them to originate from the implantation of vegetable matter. 1,2 They are usually seen in the oral mucosa, but have been described in a range of other locations, such as along the gastrointestinal or respiratory tract, the fallopian tubes, and the gallbladder. Rare cases of perianal and periprostatic pulse granulomas have also been reported.…”
mentioning
confidence: 99%
“…Positive reactions to Alcian blue at pH 2.5, indicative of acid groups such as carboxyls in plant cell walls, are also seen. 2,6,[8][9][10] Although pulse granulomas have been attributed to local degenerative changes in blood vessel walls, most authors support the exogenous foreign body theory, largely because the hyaline rings observed resemble the histologic structures of plants. 2,9,11,12 Histologic examination of the stalks of several plants that may have penetrated our patient's arm during the accident with the bale of hay showed similar shapes and staining patterns to those observed in the biopsy specimen, confirming diagnosis and etiology, which were consistent with xylem and phloem (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation